2021
DOI: 10.1007/s00464-021-08545-4
|View full text |Cite
|
Sign up to set email alerts
|

Chylous ascites in the setting of internal hernia: a reassuring sign

Abstract: Background Chylous ascites is often reported in cases with lymphatic obstruction or after lymphatic injuries such as intraabdominal malignancies or lymphadenectomies. However, chylous ascites is also frequently encountered in operations for internal hernias. We sought to characterize the frequency and conditions when chylous ascites is encountered in general surgery patients. MethodsData from patients who underwent operations for CPT codes related to open and laparoscopic abdominal and gastrointestinal surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…ChP has also been reported to occur after bariatric surgeries, mostly due to internal hernias, especially after RYGB. Sakran et al [ 13 ] for instance had undergone a systematic review of the literature and identified 38 patients from 22 case reports and one cohort study [ 14 ] with postoperative ChP. In his study, Sakran et al concluded that most of the cases were due to internal hernias after RYGB, and rarely due to iatrogenic CDI.…”
Section: Discussionmentioning
confidence: 99%
“…ChP has also been reported to occur after bariatric surgeries, mostly due to internal hernias, especially after RYGB. Sakran et al [ 13 ] for instance had undergone a systematic review of the literature and identified 38 patients from 22 case reports and one cohort study [ 14 ] with postoperative ChP. In his study, Sakran et al concluded that most of the cases were due to internal hernias after RYGB, and rarely due to iatrogenic CDI.…”
Section: Discussionmentioning
confidence: 99%
“…Our case is an unusual combination, because the chylous ascites was caused by a rare primary small bowel volvulus in an adult. The literature for mesenteric lymphatic infiltration and small bowel volvulus is scarce and focuses primarily on paediatric cases or patients with a surgery or intra-abdominal radiotherapy past [5][6][7][8][9]. Only a few case reports and small case series [10][11][12] describe this unique combination.…”
Section: Discussionmentioning
confidence: 99%
“…Athanasiadis et al [9] proposed that the presence of chylous ascites with intestinal strangulation due to internal hernia is an innocuous finding. Hayama et al [12] theorize that chylous ascites in a patient with volvulus or internal hernia is innocuous and it may reflect the patency of the mesenteric vessels.…”
Section: Discussionmentioning
confidence: 99%
“…The MCT diet had a greater effect on the reduction of chylous flow in the digestive tract and did not stop lymphatic flow production. Hence, although CL was better controlled in patients with CL after thyroid surgery, lymph leaks may be less likely to heal relative to other sites of surgery ( 33 ). This may explain the longer LOS for patients with CL after thyroid surgery.…”
Section: Discussionmentioning
confidence: 99%
“…CL is distinguished from lymphatic leakage by the pathological leakage of chylomicron rather than pure lymphocytes from broken lymphatic vessels after digestion and absorption through the gastrointestinal tract. Therefore, drainage fluid appears usually milky white or even pink ( 2 , 33 ). Whereas, short- and medium-chain triglycerides (MCTs) enter the liver directly through the hepatic portal vein ( 34 ).…”
Section: Introductionmentioning
confidence: 99%